Perancangan Alat Monitoring Kecepatan Angin Dan Arah Angin Menggunakan Komunikasi Wireleess - ichsan hu daya (Saintia Fisika, 2013)
abstract :The use of wireless communication systems (wireless) as a medium of communication in computer network system can be made by designing a system of monitoring wind speed and direction that will be sent wirelessly to a computer using a data communication at a frequency of 433.31 MHz on Module KYL 1020-U. Wind speed was measured using a censor that is connected to the wind Optocoupler cup. And for the direction of the wind is used IR LED and photodiode censors are mounted in pairs represents 8 cardinal directions. While as a data processing center, used microcontroller AVR ATMega8535. Measurements of wind speed and wind direction was made at a height of 1 meter above the ground in the area open.Systems monitoring wind speeds have approached the measurement results obtained with the standard tools of measurement results in the station Central Calibration Laboratory of Climatology  Meteorology  Climatology and Geophysics Agency (BBMKG ) Region I Field with 6,33% accuracy. The results of the design of monitoring wind direction has a resolution of 45 may indicate an 8 cardinal directions. Throw Distance wifi module is capable of transmitting data at both the coverage radius of 100 m in the open field,